Development of a Heat Transfer Analysis Software by Using Microsoft Excel - Soo, Jun Chun; Hj. Mohd Azwir bin Azlan,; Mohammad Kamil bin Abdullah, (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Heat Transfer is the study of three different modes which are conduction, convection, and radiation. However, in order to analyze the problem, it usually requires a lot of times going through lots of tables and figures to locate the data and determine the suitable formulas. Therefore, this project aims to develop a software that can analyze heat transfer problems which can help students, lectures or researchers to solve the problems in the simplest way possible. All the results should be able to obtained instantaneously after entering all the required inputs and can be dynamically updated by its own if certain input changes. The software was built by using Microsoft Excel with VBA coding and macros, while the formulas and equations used were mainly referred from the Cengel Heat Transfer textbook, 5th Ed. The developed software was able to solve most of the problems that are available in heat transfer with an accuracy up to 95%. Overall, the development process had been considered as successful and the main objective has been achieved.